2016
DOI: 10.1590/abd1806-4841.20165077
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical and immunohistochemical differences between solitary oral fibroma and fibrous papule of the face

Abstract: BackgroundThe morphological similarities between fibrous papules of the face and multiple sporadic oral fibromas were mentioned long ago and a relationship between them has been reported in the literature.ObjectiveThe aim of this study was to evaluate the participation of mast cells, elastin and collagen in a series of oral fibromas and fibrous papules of the face in order to better understand the possible role of these factors in fibrosis and the formation of these lesions.MethodsThirty cases of oral fibroma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The high presence of inflammatory cells in FPs may indicate the involvement of immunological cells in forming these lesions. Regarding the participation of inflammatory cells in extracellular matrix synthesis and remodeling, the main role is considered for mast cells and histiocytes 14,15 . These cells' secretion of potent mediators modulate fibrosis and angiogenesis, which are the main histopathological changes of FPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high presence of inflammatory cells in FPs may indicate the involvement of immunological cells in forming these lesions. Regarding the participation of inflammatory cells in extracellular matrix synthesis and remodeling, the main role is considered for mast cells and histiocytes 14,15 . These cells' secretion of potent mediators modulate fibrosis and angiogenesis, which are the main histopathological changes of FPs.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the participation of inflammatory cells in extracellular matrix synthesis and remodeling, the main role is considered for mast cells and histiocytes. 14,15 These cells' secretion of potent mediators modulate fibrosis and angiogenesis, which are the main histopathological changes of FPs. In our study, histiocytes were so prevalent that they were seen in more than a third of our cases.…”
Section: Discussionmentioning
confidence: 99%
“…Trypsin-like enzymes are proteases secreted by mast cells and are specific to mast cells. The abnormal proliferation of mast cells that synthesize trypsin-like enzymes has been detected in many lesions associated with fibrosis, such as chronic submandibular inflammation, fibrous papules, oral fibromas [47], scar formation [48] drug-induced fiber formation [49], etc. Further, TGF-β is a major regulator of fibrosis, and mast cells are also an important source of TGF-β in focal tissues.…”
Section: Mast Cellsmentioning
confidence: 99%
“…Jared et al found that, unlike wild-type C57BL/6 mice, MC-deficient mice do not develop inflammation nor do they display significant collagen deposition following silica instillation ( Brown et al, 2007 ). MCs also secrete tryptase, which interacts with multiple regulatory factors, such as activating proteinase-activated receptor 2 (PAR2), inducing DNA synthesis in resting fibroblasts and promoting collagen synthesis, thereby stimulating fibroblast proliferation ( Henriques Á et al, 2016 ). Collectively, these studies highlighted a clear involvement of MCs in silicosis.…”
Section: Introductionmentioning
confidence: 99%